Diffusion of the Discourse on Love of Reading in Europe from the 18th till the 20th Century - Mäkinen, Ilkka (Knygotyra, 2020)
When reading in the 18th century became an activity common among an ever growing part of the European population and thereby a socially more visible cultural phenomenon, a need arose to create concepts and linguistic terms to refer to the new types of reading behavior. The new masses of readers did not seemingly have a rational goal for their reading, they just read for the sake of reading itself. Therefore, an explanation for their behavior was that they had a love of reading. To speak about people’s love of reading became a recurrent feature of the discourse on reading, a sub-discourse of its own, the discourse on the love of reading. The birthplace of the discourse may have been in 17th century France, wherefrom it was mediated into other countries and language areas. Even the contemporaries believed that the reading mania was contagious, and expected, feared, or hoped that something similar would happen in their own country. This caused debate and the use, even invention, of words and phrases that belong to the discourse on love of reading. Even the words and phrases used for speaking about reading migrated over linguistic, political, and social borders. The initiation, growth, and diffusion of the discourse can be followed by searching the typical words and phrases that indicate the presence of the discourse. Data were obtained from Google Books Ngram Viewer and national full-text databases of books and newspapers. A map representing the geographical diffusion of the discourse in Europe until the 20th century is constructed. The historical conditions for the diffusion of the discourse are discussed. Methodological problems are discussed and future research is outlined.
Keywords: history of reading; love of reading; discourse on reading; motivation for reading; cultural history; Europe